2014
DOI: 10.1161/strokeaha.114.004761
|View full text |Cite
|
Sign up to set email alerts
|

High-Resolution Magnetic Resonance Wall Imaging Findings of Moyamoya Disease

Abstract: Background and Purpose-Diagnosis of Moyamoya disease (MMD) is based on the characteristic angiographic findings.However, differentiating MMD from intracranial atherosclerotic disease (ICAD) is difficult. We compared vessel wall imaging findings on high-resolution magnetic resonance imaging between MMD and ICAD. Methods-High-resolution magnetic resonance imaging was performed on 32 patients with angiographically proven MMD and 16 patients with acute infarcts because of ICAD. Bilateral internal carotid arteries … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
105
2

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 162 publications
(112 citation statements)
references
References 13 publications
5
105
2
Order By: Relevance
“…Because of the increasing number of elderly patients with MMD, 19 differential diagnosis between MMD and atherosclerotic occlusive cerebrovascular disease is becoming more important. Although advantages of high-resolution MR wall imaging for the differential diagnosis between MMD and atherosclerosis have been reported, 20 ultrasonography would be helpful to differentiate these 2 diseases with respect to the morphologically different features of their vessel walls. Especially in young children, sedation is sometimes necessary to perform MR imaging, but not carotid ultrasonography.…”
Section: Discussionmentioning
confidence: 99%
“…Because of the increasing number of elderly patients with MMD, 19 differential diagnosis between MMD and atherosclerotic occlusive cerebrovascular disease is becoming more important. Although advantages of high-resolution MR wall imaging for the differential diagnosis between MMD and atherosclerosis have been reported, 20 ultrasonography would be helpful to differentiate these 2 diseases with respect to the morphologically different features of their vessel walls. Especially in young children, sedation is sometimes necessary to perform MR imaging, but not carotid ultrasonography.…”
Section: Discussionmentioning
confidence: 99%
“…20,[30][31][32][33][34] This method can use highresolution 2D or 3D imaging, frequently with pre-and postcontrast T1 or proton-attenuation sequences. 20,32,[35][36][37][38] In addition, high-resolution T2-weighted imaging can be used for multicontrast imaging.…”
Section: Vessel Wall Imagingmentioning
confidence: 99%
“…20,32,[35][36][37][38] In addition, high-resolution T2-weighted imaging can be used for multicontrast imaging. 33,[39][40][41] In contradistinction to conventional angiographic imaging techniques that primarily evaluate the blood vessel lumen, such as conventional angiography, this approach provides information regarding the blood vessel wall itself, which is typically only 1-2 mm thick in proximal intracranial vessels. 42 VWI has been described as black-blood imaging because it results in low signal in the vessel lumen, thereby aiding in the visualization of the blood vessel wall.…”
Section: Vessel Wall Imagingmentioning
confidence: 99%
“…39 These VW-MR imaging findings are consistent with histopathologic studies showing thinning of the arterial media and a paucity of inflammatory cells in the vessel wall of patients with Moyamoya disease. 40 However, a subsequent study 41 found a considerably higher frequency of concentric internal carotid and middle cerebral artery wall enhancement in patients diagnosed with Moyamoya disease and, perhaps surprisingly, no difference in vessel wall enhancement between early and late angiographic stages of the disease. Further research is needed to resolve the discordance among studies.…”
mentioning
confidence: 95%